Kurt Vonnegut's America - Klinkowitz, Jerome (University of South Carolina Press, 2009)
Following an introduction characterizing Vonnegut as Klinkowitz came to know him over the course of their friendship, this study charts the impact of Vonnegut on American society and of that society on Vonnegut for more than a half-century to illustrate how each informed the other. --from publisher description.